1980
DOI: 10.1093/jn/110.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanism of Protein-Induced Hypercalciuria in Older Men and Women

Abstract: A human metabolic study was conducted to observe the effect of level of protein intake on urinary calcium, calcium absorption and calcium balance in older adults and to further study the mechanisms of protein-induced hypercalciuria. An increase in protein intake from about 47 to 112 g while maintaining calcium, magnesium and phosphorus intakes constant caused an increase in urinary calcium and a decrease in calcium retention. Glomerular filtration rate was increased and fractional renal tubular reabsorption wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
2
4

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(78 citation statements)
references
References 26 publications
5
67
2
4
Order By: Relevance
“…Although the reason(s) why a high protein diet increases urinary Ca excretion has been investigated in men (20)(21)(22)(23)(24)(25), rats (3, 6-8, 9, 26-28), and sheep (29), it is not yet completely elucidated. Schuette et al suggested that mild metabolic acidosis resulting from the oxidation of excess amino acids would be responsible for a depressed Ca reabsorption by renal tubule cells, leading to hypercalciuria in men (21,24).…”
Section: Discussionmentioning
confidence: 99%
“…Although the reason(s) why a high protein diet increases urinary Ca excretion has been investigated in men (20)(21)(22)(23)(24)(25), rats (3, 6-8, 9, 26-28), and sheep (29), it is not yet completely elucidated. Schuette et al suggested that mild metabolic acidosis resulting from the oxidation of excess amino acids would be responsible for a depressed Ca reabsorption by renal tubule cells, leading to hypercalciuria in men (21,24).…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated in Fig. 15B, when acid production is increased by the administration of wheat gluten and lactalbumin (66), egg white (1) or methionine (41), the resulting increases from control in urinary net acid excretion are less than the increases in acid production, as estimated by the increases in urinary SO 4 excretion, the slope of the regression line being significantly Ͻ1. Thus renal compensation, in terms of increased net acid excretion, Fig.…”
Section: Relationship Of Ca Balances To Acid Balances In Healthy Humamentioning
confidence: 97%
“…It was also demonstrated that high protein diets produced an increase in total renal acid, ammonium, and sulfate excretions whereas urinary sodium excretion decreased in human subjects (17)(18)(19). Zemel et al (20) showed that SAA added to the low protein diet also caused urinary calcium to increased.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators observed that the hypercalciuria caused by the high protein intake was due to the decrease in fractional tubular reabsorption of calcium and to the increase in glomerular filtration rate (8,9,(15)(16)(17). Hegsted and Linkswiler (9) reported that these changes were exhibited long term, i.e., over the 60-day experimental period.…”
Section: Discussionmentioning
confidence: 99%